The Influence of Specific towards the Bank Performance Listed on the Indonesian Stock Exchange - Muroqi, Achmad; Irawan, Andi; Upekca, I Wayan Astu; SL, Henny; Margaretha, Farah (Quantitative Economics and Management Studies, 2024)
This study investigates the influence of specific financial variables on the performance of banks listed on the Indonesia Stock Exchange. The research employs a quantitative approach using secondary data obtained from financial reports and annual reports of listed banks over a five-year period from 2019 to 2023. These data were sourced from the official website of the Indonesia Stock Exchange and individual bank websites. The analysis was conducted using regression analysis with the assistance of EViews 12 software. The results indicate that Capital Adequacy (CA) significantly affects Return on Assets (ROA) based on the Fixed Effect Model (FEM), Chow Test, and Random Effect Model (REM) analysis. The statistical tests confirm that variations in CA contribute to differences in bank performance, emphasizing the critical role of capital adequacy in determining profitability. The findings of this study suggest that capital adequacy is a key determinant of bank performance, highlighting its importance in maintaining financial stability and operational efficiency. Understanding the impact of financial variables on performance can help stakeholders assess the financial health of banks and make informed decision.